Design optimization of Micro Air Launch Vehicle using differential evolution - Aldheeb, Mohammed; Kafafy, Raed; Idres, Moumen; Omar, Hanafy; Abido, Mohammad (Instituto de Aeronautica e Espaco-IAE - Brazil, 2012)
In this paper, we have used the differential evolution to optimize the design of a Micro Air Launch Vehicle and its launch trajectory. Since trajectory design of a launch vehicle requires prior knowledge of the masses and propulsion performance parameters of the Micro Air Launch Vehicle, whereas the vehicle design requires prior knowledge of the required velocity